1999
DOI: 10.1074/jbc.274.39.27839
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Epithelial Response of a Papillomavirus Promoter to Transcriptional Activators

Abstract: Mucosal epitheliotropic papillomaviruses have a similar long control region (LCR) organization: a promoter region, an enhancer region, and a highly conserved distribution of E2 DNA binding sites. The enhancer of these viruses is epithelial-specific, as it fails to activate transcription from heterologous promoters in nonepithelial cell types (Gloss, B., Bernard, H. U., Seedorf, K., and Klock, G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…Higher quercetin concentrations did not result in further increase of p27 Kip1 promoter activity (data not shown). The pGL3TK plasmid in which the tk promoter directs expression of luciferase (Vance et al, 1999) was used as a control to examine whether any possible effect observed was specific for the p27…”
Section: Quercetin Treatment Activates the P27mentioning
confidence: 99%
“…Higher quercetin concentrations did not result in further increase of p27 Kip1 promoter activity (data not shown). The pGL3TK plasmid in which the tk promoter directs expression of luciferase (Vance et al, 1999) was used as a control to examine whether any possible effect observed was specific for the p27…”
Section: Quercetin Treatment Activates the P27mentioning
confidence: 99%
“…The E2 protein forms homodimers and recognizes and binds to 12bp palindromic DNA sequences in the transcriptional control region of HPV (4). E2 can then regulate transcription from the adjacent promoter that controls the expression of the HPV oncogenes E6 and E7; E2 can either activate or repress transcription depending upon E2 protein levels and the cell type (5,6). As well as regulating transcription E2 is also essential for replication of the viral genome; there are three E2 DNA binding sequences surrounding the viral origin (ori) of replication and a physical interaction between E2 and E1 results in recruitment of E1 to the ori sequence (7,8,9).…”
mentioning
confidence: 99%
“…Construction of the PV2 6E2 and tk 6E2 reporter constructs has been described previously (39). The lcr/tk hybrid promoter was generated by splicing-by-overlap-extension PCR.…”
Section: Methodsmentioning
confidence: 99%
“…This epithelial preference is not extended to heterologous promoters such as the thymidine kinase (tk) promoter. This was the first time that a level of epithelial specificity has been shown to reside in a papillomavirus promoter region (39).…”
mentioning
confidence: 95%
See 1 more Smart Citation